Reliability analysis for subsea pipeline cathodic protection systems / - Trille, Christophe (Cranfield University, 1996)
Subsea pipelines, as the main transportation means for oil and gas produced offshore, are a key element of the production system. Cathodic protection systems (CPS) are used in combination with surface coatings to protect the pipeline from external corrosion. Although cases of pipeline failure due to external corrosion remain rare, such failures can have catastrophic effects in terms of human lives, environment degradation and financial losses. The offshore industry was led to the use of risk analysis techniques subsequent to major disasters, such as Piper Alpha and Alexander Kjelland. These accidents made the development and use of risk analysis techniques of highly significant interest, and reliability analysis is presently becoming a more important management tool in that field for determining reliability of components such as pipelines, subsea valves and offshore structures. This research is based on an analysis of subsea pipeline cathodic protection systems and on a model of the electrochemical potentials at the pipeline surface. This potential model uses finite element modelling techniques, and integrates probabilistic modules for taking into account uncertainties on input parameters. Uncertainties are used to calculate standard deviations on the potential values. Based on the potentials and potential variances obtained, several parameters characteristic of the cathodic protection system reliability, such as probability of failure and time to failure, are calculated. The model developed proved suitable for simulating any pipeline, under any environmental and operational conditions. It was used as a reliability prediction tool, and to assess the effects of some parameters on the cathodic protection system reliability.